2019
DOI: 10.1021/jacs.9b08243
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Origins of Enantioselectivities in Spirobiindane-Based Hypervalent Iodine(III)-Induced Asymmetric Dearomatizing Spirolactonizations

Abstract: The work of Kita et al. on asymmetric oxidative dearomatization of naphthol carboxylic acids to spirolactones mediated/catalyzed by a novel, conformationally rigid μ-oxo-bridged hypervalent iodine­(III) species is a landmark discovery in enantio­selective iodine­(III) catalysis [Kita, Y.; et al. Angew. Chem., Int. Ed. 2008, 47, 3787. DOI: 10.1002/anie.200800464; J. Am. Chem. Soc. 2013, 135, 4558. DOI: 10.1021/ja401074u]. We have investigated the detailed mechanism of this important transformation using density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…This, due to the strongly electron‐withdrawing nature of the hypervalent iodine, primes the attack of the nucleophile on the ring (pathway 1; TS1 ), resulting in simultaneous dearomatization and reduction of iodine. Such a mechanism has been supported by the recent computational study by Houk and Xue on the asymmetric spirolactonization, wherein it has been shown to proceed via a feasible energy barrier (≈21 kcal mol −1 ) and to reproduce the experimentally observed enantioselectivity . In the second mechanistic pathway, often referred to as dissociative, intermediate A undergoes a unimolecular fragmentation, reducing iodine and yielding phenoxenium ion B (pathway 2; TS2 ).…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…This, due to the strongly electron‐withdrawing nature of the hypervalent iodine, primes the attack of the nucleophile on the ring (pathway 1; TS1 ), resulting in simultaneous dearomatization and reduction of iodine. Such a mechanism has been supported by the recent computational study by Houk and Xue on the asymmetric spirolactonization, wherein it has been shown to proceed via a feasible energy barrier (≈21 kcal mol −1 ) and to reproduce the experimentally observed enantioselectivity . In the second mechanistic pathway, often referred to as dissociative, intermediate A undergoes a unimolecular fragmentation, reducing iodine and yielding phenoxenium ion B (pathway 2; TS2 ).…”
Section: Introductionmentioning
confidence: 82%
“…In particular, the substantial rate enhancement with the increaseo fw ater content speaks strongly against the dissociative mechanism (Scheme 2, pathway 2), in which H 2 Oi se ngaged only after the rate-determining dissociation of intermediate A.T his is furtherr einforced by the large negative entropyo f activation,u nlikely for ad issociative process.T he measured experimental free energy barrier (22-23 kcal mol À1 )i sa lso considerably lower than that determined computationally for pathway 2( > 28 kcal mol À1 ), [7] but in agreement to those computed for pathways 1a nd 3( 21-24 kcal mol À1 ). [6,9] However,t he computational studies on the associativem echanisms have shown that in both the transition states of type TS1 and TS3 (Scheme 2, pathways 1a nd 3) for the barriers to be feasible, the attack of nucleophile must proceed with as imultaneous deprotonation by an acetate anion (not shown in the scheme). [6,9] This is, however,inconsistent with the lack of asolvent kinetic isotope effect upon the exchange of H 2 Of or D 2 O. Overall,t he data allows with high confidence to discard the pathways shown in Scheme 2a st he correct reactionm echanisms.…”
Section: Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, they reported that the slight modification in catalyst backbone enhanced the enantioselectivity of the dearomatizing‐spirolactonization of naphthols . Recently, Houk and coworkers studied a thorough mechanism of this significant protocol by density functional theory (DFT) . In this study, it was found that the proton transfer occurred from the tethered acid of naphthols to the linking oxygen atom or the ligand of iodine(III).…”
Section: Synthetic Strategies Towards Spirobutenolides and Spirobutyrmentioning
confidence: 99%